2018
DOI: 10.14743/apem2018.2.281
|View full text |Cite
|
Sign up to set email alerts
|

In-process non-destructive ultrasonic testing application during wire plus arc additive manufacturing

Abstract: Additive manufacturing is a technique which builds structures by depositing material in a layer-by-layer manner. Wire plus arc additive manufacturing technology also belongs into this group of manufacturing processes. It has been investigated in the last twenty-five years, although the first patent dates from 1925. Wire plus arc additive manufacturing uses existing welding equipment, an electric arc as the heat source, and wire as the feedstock. In this paper, we explain some basic process planning and impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Unlike the existing 3D printing technologies which require heat to melt material [23][24][25], SP3D is a kinetic process. Metal particles are accelerated up to Mach 3 [26].…”
Section: Spee3d Printing Of Coppermentioning
confidence: 99%
“…Unlike the existing 3D printing technologies which require heat to melt material [23][24][25], SP3D is a kinetic process. Metal particles are accelerated up to Mach 3 [26].…”
Section: Spee3d Printing Of Coppermentioning
confidence: 99%
“…Wang et al [14] demonstrated that processing parameters had impacted the dimensional accuracy, microstructure, and mechanical properties of aluminium alloy components using GTAW based WAAM. Besides that, the quality of the manufacturing component depends primarily on the geometry of the single bead to prevent issues like excessive weld bead and insufficient bonding occur [15]. However, many input process parameters are time-consuming and influenced by complex interaction among various process parameters, which cause challenges to the parametric selection combination [16].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, UT uses a couplant (liquid) between the probe and the test part. The introduction of the couplant introduces special test considerations since the part will be placed in a liquid [13]. UT can be combined with special equipment in which the couplant is not required, such as laser ultrasonic testing (LUT).…”
Section: Summary Non-destructive Testing Techniques In Ammentioning
confidence: 99%
“…Piezoelectric Excitation setup (left) and PZT attachment (right)The first experiment consisted of testingBars 1,2 ,6,7,13,14,21,24,25, 28, 32, 36, 39, and 42 (…”
mentioning
confidence: 99%